SEAFARER – A new concept for validating radiotherapy patient specific QA for clinical trials and clinical practice. (June 2022) - Lehmann, Joerg; Hussein, Mohammad; Barry, Miriam A.; Siva, Shankar; Moore, Alisha; Chu, Michael; Díez, Patricia; Eaton, David J.; Harwood, Jeffrey; Lonski, Peta; Claridge Mackonis, Elizabeth; Meehan, Carole; et al.
Highlights: Patient specific quality assurance can miss clinically significant errors in SABR plan deliveries. Remote auditing of the sensitivity of patient specific quality assurance is feasible. Assessing the sensitivity of clinically used patient specific quality assurance procedures is a new concept for dosimetry audits. Abstract: Background: The quality of radiotherapy delivery has been shown to significantly impact clinical outcomes including patient survival. To identify errors, institutions perform Patient Specific Quality Assurance (PSQA) assessing each individual radiotherapy plan prior to starting patient treatments. Externally administered Dosimetry Audits have found problems despite institutions passing their own PSQA. Hence a new audit concept which assesses the institution's ability to detect errors with their routine PSQA is needed. Methods: Purposefully introduced edits which simulated treatment delivery errors were embedded into radiation treatment plans of participating institutions. These were designed to produce clinically significant changes yet were mostly within treatment delivery specifications. Actual impact was centrally assessed for each plan. Institutions performed PSQA on each plan, without knowing which contained errors. Results: Seventeen institutions using six radiation treatment planning systems and two delivery systems performed PSQA on twelve plans each. Seventeen erroneous plans (across seven institutions) passed PSQA despite causing >5% increase in spinal cord dose relative to the original plans. Six plans (from four institutions) passed despite a >10% increase. Conclusions: This novel audit concept evolves beyond testing an institution's ability to deliver a single test case, to increasing the number of errors caught by institutions themselves, thus increasing quality of radiation therapy and impacting every patient treated. Administered remotely this audit also provides advantages in cost, environmental impact, and logistics.